Mechanisms of carcinogenic activity triggered by lysine-specific demethylase 1A - Yang, Chao; Li, Dan; Zang, Shaohong; Zhang, Lei; Zhong, Zhangfeng; Zhou, Yingtang (Frontiers in Pharmacology, 2022)
Epigenetics has emerged as a prime focus area in the field of cancer research. Lysine-specific demethylase 1A (LSD1), the first discovered histone demethylase, is mainly responsible for catalysing demethylation of histone 3 lysine 4 (H3K4) and H3K9 to activate or repress gene transcription. LSD1, which is abnormally expressed in various cancers, participates in cancer proliferation, apoptosis, metastasis, invasion, drug resistance, and other processes by interacting with regulatory factors and is a potential therapeutic target for cancers. This review summarises the major oncogenic mechanisms mediated by LSD1 and provides a reference for developing novel and efficient anticancer strategies targeting LSD1.